Bleeding complications of triple antithrombotic therapy after percutaneous coronary interventions. Issue 2 (24th May 2016) - Faza, Nadeen N.; Mentias, Amgad; Parashar, Akhil; Chaudhury, Pulkit; Barakat, Amr F.; Agarwal, Shikhar; Wayangankar, Siddharth; Ellis, Stephen G.; Murat Tuzcu, E.; Kapadia, Samir R.
Abstract : Background: 5% of patients undergoing coronary stenting have an indication for anticoagulation. The aim of our study was to determine the bleeding rates and complications in patients on triple oral antithrombotic therapy (TOAT) after coronary stenting. Methods: We studied patients who underwent coronary stenting in our institution between 2003‐2013 and were started on TOAT. Bleeding was the primary outcome. Results: Totally, 999 patients were treated with TOAT with a median follow up of 127 days. All patients were treated with warfarin as an anticoagulant. 267 patients (26.7%) developed a total of 331 bleeding events. 100 patients had bleeding during the first 30 days of therapy. Major bleeding, minor bleeding, bleeding requiring medical attention, and minimal bleeding developed in 2.9%, 3.3%, 17.2%, and 3.3% of the patients respectively as their most significant bleeding event. Patients with anticoagulation initiated at time of stenting had a significantly higher bleeding rate compared to those already on chronic anticoagulation [adjusted HR (95% CI): 1.37 (1.03–1.79), P  = 0.03]. The bleeding likelihood was significantly higher for patients with drug‐eluted stents (DES) compared to bare‐metal stents (BMS) [adjusted OR (95% CI): 1.52 (1.14 − 2.04), P  < 0.05]. Patients with atrial fibrillation had an increased rate of bleeding after 6 month of initiation of TOAT with significantly worse outcomes. Conclusions: TOAT after coronary stenting is associated with high bleeding rates. Patients with AF had worse outcomes. Patients with newly initiated anticoagulation at time of stenting bleed significantly more than people already on chronic anticoagulation prior to stenting. © 2016 Wiley Periodicals, Inc.